Változások a családban: Orsolya Kolozsvari (2019): Gender, Marriage, Families – From the Individual to the Social. Kendall Hunt Publishing Company, Dubuque, 372 p. - Béres, Zsuzsa; Ladancsik, Tibor; Maszlag, Fanni; Nemes-Zámbó, Gabriella (METSZETEK Társadalomtudományi Folyóirat, 2022)
-